127 Modifiable Cardiovascular Risk Profile in People with Mild Cognitive Symptoms Attending a Memory Service - an Opportunity to Promote Brain Health. (16th September 2019) - Dookhy, Joshi; McHale, Cathy; Kennelly, Sean; Coughlan, Tara; Collins, Ronan; Ryan, Dan; O'Neill, Desmond
Abstract: Background: Current evidence strongly implicates the burden of vascular risk factors (VRF) in the development of stroke, cognitive decline and dementia. This effect is mediated through several mechanisms, including amyloidogenesis, chronic neuroinflamation, cerebral perfusion and white-matter changes. Vascular risk profiling is well-embedded in stroke and cardiac services, but less so in memory services. Methods: A review of established modifiable VRF (hypercholesterolemia, Body Mass Index (BMI), hypertension, HbA1c, smoking and alcohol habits) of people with mild cognitive complaints (mild cognitive impairment and subjective memory decline) in a memory service was performed. Risk factors measured in clinic were classified as: systolic ≥140mmHg / diastolic ≥90mmHg hypertension; LDL cholesterol >3mmol/l; HbA1c >39mmol/mol; weekly alcohol >21units; smoking and BMI >24.9kg/m 2 . Data was recorded and analysed using Microsoft Excel. Results: Thirty-seven people, including 16 females (mean age 71.4, range of 49-83 years), were reviewed. 13/37 (35%) were aged ≤69 years. A total of 91 VRFs were identified in the study population. 29/37 (78%) had ≥2 VRF present. 3/37 (8%) had five VRF. 18/37 (49%) had prior history of either stroke, vascular or heart disease. Five of thirty-seven, (13.5%) and 13/37 (35%) were current and ex-smokers respectively, 2/37 (5%) consumed excess alcohol, 24/37 (65%) had elevated BMI and 11/37 (30%) had elevated LDL cholesterol. 21/37 (57%) had hypertension. Of these, 11/21 were known but poorly-controlled and 10/21 were identified de novo. All of the 32% (12/37) who had hyperglycaemia were de novo. Conclusion: This study highlights the high prevalence of unidentified or poorly controlled VRF in people with mild cognitive symptoms attending a memory service. Given its importance to brain health and mitigation of future cognitive decline, a structured focus on identifying and managing these VRF in this setting is necessary. Exercise-based lifestyle programs should be embedded in post-diagnostic services for this population.